Combination of ginsenoside Rb1 and Rd protects the retina against bright light-induced degeneration - Minjuan Bian (Nature Portfolio, 2017)
Abstract Photoreceptor degeneration is a central pathology of various retinal degenerative diseases which currently lack effective therapies. Antioxidant and anti-inflammatory activities are noted for Panax notoginsenoside saponins (PNS) and related saponin compound(s). However, the photoreceptor protective potentials of PNS or related saponin compound(s) remain unknown. The current study revealed that PNS protected against photoreceptor loss in bright light-exposed BALB/c mice. Combination of ginsenoside Rb1 and Rd, two major saponin compounds of PNS, recapitulated the retinal protection of PNS and attenuated retinal oxidative stress and inflammatory changes. Rb1 or Rd partially alleviated all-trans-Retinal-induced oxidative stress in ARPE19 cells. Rb1 or Rd suppressed lipopolysaccharides (LPS)-induced proinflammatory gene expression in ARPE19 and RAW264.7 cells. Rb1 or Rd also modulated the expression of proinflammatory microRNA, miR-155 and its direct target, anti-inflammatory SHIP1, in LPS-stimulated RAW264.7 cells. The retinal expression of miR-155 and SHIP1 was altered preceding extensive retinal damage, which was maintained at normal level by Rb1 and Rd combination. This work shows for the first time that altered expression of miR-155 and SHIP1 are involved in photoreceptor degeneration. Most importantly, novel retinal protective activities of combination of Rb1 and Rd justify further evaluation for the treatment of related retinal degenerative disorders.